Hippocratic Diagnosis, Solomonic Therapy, Roman Amulets Epilepsy, Exorcism, and the Diffusion of a Jewish Tradition in the Roman World - Zellmann-Rohrer, Michael (2022)
Two contrasting portraits of exorcism in the Roman period for patients with symptoms consistent with epilepsy, drawn by Josephus (A.J. 8.45–47) and Lucian (Philops. §16), illustrate a substantial albeit contested diffusion of that ancient technique from the Jewish tradition to a wider Mediterranean public. The process is reflected in a similarly complex traditional background and textual composition of a group of inscribed Greek amulets for epilepsy. A sidelight on attitudes towards the practice of exorcism, on its way to wider popularity, and the conception of epilepsy is cast by these amulets, which have not yet been studied as a group. Their texts witness the application of precise Greek medical terminology, yet to an end, and in a compositional company, that authors in the Hippocratic tradition would have rejected. More generally, the artifacts offer a cross-section of amuletic practice and its diversity in the Roman and late ancient periods.
Keywords: Medicine; Amulets; Exorcism; Epilepsy